Recurrence of hepatitis C after liver transplantation is associated with increased systemic IL-10 levels. Issue 1 (2001) - Sheiner, Patricia A.; Florman, Sander S.; Emre, Sukru; Fishbein, Thomas; Schwartz, Myron E.; Miller, Charles M.; Boros, Peter
Abstract : Background : Recurrence of hepatitis C after liver transplantation is an almost universal occurrence. T-cell derived cytokines have an important role in the development of liver damage associated with chronic hepatitis C, their post-transplant levels, however, have not been correlated with histologic recurrence of the disease. Aims : We sought to analyze levels of TNF-α, soluble IL2 receptor, IL-4 and IL-10 at 1 month, 6 months and 1 year after transplantation in 27 patients undergoing transplantation for hepatitis C related end-stage liver disease. Methods : HCV RNA levels were monitored by a branched-chain DNA signal amplification assay. Diagnosis of recurrent hepatitis was based on 1-year protocol biopsies and on biopsies performed for liver enzyme elevations. Results : Recurrent hepatitis C was detected in 52% ( n =14) of the 27 patients. HCV RNA levels rose over time in all patients regardless of histologic recurrence. TNF-α, and IL-4 levels, although elevated, did not show specific patterns over time or in correlation with recurrence. Similarly, the early elevation followed by a gradual decrease over the first year in the amount of soluble IL-2 receptor was not related to histologic recurrence. We observed a significant increase in circulating IL-10 levels over the first year in patients with biopsy-proven recurrence, while patients with no signs of histologic recurrence displayed increased, but steady levels. Conclusions : These results suggest that while these cytokines are associated with post-transplant recurrence of hepatitis C, their production may be altered by additional factors.